On the Risk of a Fall in Household Consumption in Norway - Bjørn Helge Vatne (Norges Bank, 2014)
This paper utilises household level data from administrative registers to illustrate that Norwegian households' high debt-to-income and loan-to-value ratios could prompt an increase in household saving in the event of a rise in interest rates and/or a fall in house prices. Both higher direct net interest expenses and higher principal payments could displace consumption. The effect will depend on the financial situation of each household. If we assume a 3 percentage point increase in interest rates and a 30 percent fall in house prices, the calculations indicate that total household income available for consumption could fall by as much as 8 percent.
hdl:11250/2506902
Keywords: 330